Seasonal Hypomagnesemia in reindeer on Kautokeino winter pasture in Finnmark County, Norway - Hoff, Bernt; Rognmo, Arne; Havre, Gustav; Morberg, Hanne (Rangifer, 1993)
Hypomagnesemia was diagnosed in reindeer on Kautokeino winter pasture in Finnmark County, Norway. The affected animals were paretic or ataxic. Mean serum magnesium levels were 0.19 +/- 0.20 mm/L (n = 6), compared to a serum Mg level of 0.82 +/- 0.17 mm/L for the reference group.